Coconut Avenue, Trinidad, B.W.I. - (:unkn) unknown (My University, 2010)
This photograph shows a long stretch of flat road flanked on both sides with tall, mature, coconut palms, although at least one of the coconut trees at centre left is a young one. The coconut palms resemble moko jumbies or stilt walkers or dancers playing on this deserted country road.
Colour: Black and White; Style: Portrait; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Rural roads--Trinidad and Tobago; Coconut palm--Trinidad and Tobago; Trees--Trinidad and Tobago; 1939